2022
DOI: 10.3390/biomedicines10030675
|View full text |Cite
|
Sign up to set email alerts
|

New Frontiers of Extracorporeal Shock Wave Medicine in Urology from Bench to Clinical Studies

Abstract: A shock wave (SW), which carries energy and propagates through a medium, is a type of continuous transmitted sonic wave that can achieve rapid energy transformations. SWs have been applied for many fields of medical science in various treatment settings. In urology, high-energy extracorporeal SWs have been used to disintegrate urolithiasis for 30 years. However, at lower energy levels, SWs enhance the expression of vascular endothelial growth factor (VEGF), endothelial nitric oxide synthase (eNOS), proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 123 publications
0
12
0
3
Order By: Relevance
“…ESWT in recent years has emerged as a valuable treatment method for various neurological and musculoskeletal disorders [ 13 , 14 ]. Animal studies reported that ESWT produced chondroprotective [ 15 ], anti-inflammatory [ 16 ], neovascularization [ 17 ], anti-apoptotic [ 18 ], and tissue regeneration effects [ 19 ], which could be relevant in the treatment of OA. A recent systematic review and meta-analysis of 14 studies that included 782 participants with knee OA suggested that ESWT is an effective treatment for relieving pain and enhancing the functional status of knee OA patients without any significant adverse effects [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…ESWT in recent years has emerged as a valuable treatment method for various neurological and musculoskeletal disorders [ 13 , 14 ]. Animal studies reported that ESWT produced chondroprotective [ 15 ], anti-inflammatory [ 16 ], neovascularization [ 17 ], anti-apoptotic [ 18 ], and tissue regeneration effects [ 19 ], which could be relevant in the treatment of OA. A recent systematic review and meta-analysis of 14 studies that included 782 participants with knee OA suggested that ESWT is an effective treatment for relieving pain and enhancing the functional status of knee OA patients without any significant adverse effects [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acidic ejaculate (pH < 7.2) may be associated with obstruction of seminal vesicles, while alkaline ejaculate (pH > 8.0) may be related to MAGI and consequent inflammation 11 . The decrease in pH in our cohort could be explained by the anti‐inflammatory activity of the shock waves 31–33 . However, evidence on the correlation between seminal pH and other seminal parameters (e.g., number, motility) or clinical outcomes (e.g., pregnancy rate) is still limited 34–36 …”
Section: Discussionmentioning
confidence: 77%
“…11 The decrease in pH in our cohort could be explained by the anti-inflammatory activity of the shock waves. [31][32][33] However, evidence on the correlation between seminal pH and other seminal parameters (e.g., number, motility) or clinical outcomes (e.g., pregnancy rate) is still limited. [34][35][36]…”
Section: Kalla Et Al Published the First Article On The Impact Of Sho...mentioning
confidence: 99%
“…LESW was shown to be effective for temporarily increasing tissue permeability and the intravesical delivery of Botox for the treatment of OAB in animal studies and in a human clinical trial [ 31 ]. Our preliminary study using LESW and intravesical BoNT-A instillation every week in OAB patients also demonstrated an improvement in the Global Response Assessment without any adverse events [ 32 ].…”
Section: Clinical Application Of Botox On Oab: Efficacy Adherence Adv...mentioning
confidence: 99%